Nicotine induces a dual effect on the beige-like phenotype in adipocytes - Chen, Hui-jian; Xiang, Jie; Zhang, Wan-xia; Sun, Ao; Li, Gai-ling; Yan, You-e (Archives of Biological Sciences, 2019)
Paper description: The influence of nicotine on the beige-like phenotype in adipocytes has not been examined. We detected the expression of beige-related genes and proteins at different stages of differentiation of the preadipocyte 3T3-L1 cell line. Nicotine, acting on different stages of 3T3-L1 differentiation, produced a dual effect on the expression of beige-related genes and proteins, inducing dysfunction in beige-like adipocytes. This activity can affect thermogenesis in adipose tissue and cause dysfunctional fat metabolism. Abstract: Nicotine, the main component of cigarette smoke, affects white/brown adipocytes. Few studies have concentrated on beige adipocytes. In this study, 3T3-L1 cells were differentiated in the presence of nicotine (25, 50 and 100 µmol/L) during early differentiation and maintenance stages. Cell viability and the state of lipid droplets were assessed by the MTT assay and Oil Red O, respectively, and the expression of beige-related genes and proteins was examined by RT-qPCR, Western blotting and flow cytometry. Nicotine did not alter adipocyte differentiation; however, it increased the expression of peroxisome proliferator-activated receptor gamma (PPARγ) protein during early differentiation and maintenance. Nicotine treatment during early differentiation downregulated gene and protein expression of PPARγ coactivator 1-alpha (PGC-1α), uncoupling protein 1 (UCP1) and cluster of differentiation 137 (CD137), and gene expression of Cbp/p300 interacting transactivator with Glu/Asp rich carboxy-terminal domain 1 (Cited1), transmembrane protein 26 (Tmem26), and short stature homeobox 2 (Shox2). Nicotine treatment during the maintenance stage upregulated these beige-related genes/proteins. Nicotine treatment of immature adipocytes damaged beige function through a decrease in PGC-1α/UCP1 expression, but nicotine treatment of mature adipocytes or both immature and mature cells enhanced beige functioning. Nicotine induced beige-like phenotype dysfunction in 3T3-L1 adipocytes. This process may affect thermogenesis in adipose tissue and cause a dysfunction in fat metabolism. https://doi.org/10.2298/ABS190403037C Received: April 3, 2019; Revised: June 10, 2019; Accepted: June 14, 2019; Published online: July 6, 2019 How to cite this article: Chen H, Xiang J, Zhang W, Sun A, Li G, Yan Y. Nicotine induces a dual effect on the beige-like phenotype in adipocytes. Arch Biol Sci. 2019;71(3):533-40.